2010
DOI: 10.1021/jp102555c
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning the Dispersion and the Mobility of BaO Domains on NOx Storage Materials via TiO2 Anchoring Sites

Abstract: In an attempt to control the surface dispersion and the mobility of BaO domains on NO x storage materials, TiO 2 /TiO x anchoring sites were introduced on/inside the conventional γ-Al 2 O 3 support matrix. BaO/TiO 2 / Al 2 O 3 ternary oxide materials were synthesized via two different sol-gel preparation techniques, with varying surface compositions and morphologies. The synthesized NO x storage materials were studied via XRD, Raman spectroscopy, BET surface area analysis, TPD, XPS, SEM, EDX-mapping, and in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 48 publications
6
63
0
Order By: Relevance
“…Titanium (IV) isopropoxide (TIP, 97%, Sigma-Aldrich) and aluminum-tri-sec-butoxide (ASB, 97%, Sigma-Aldrich) were used as the main ingredients in the preparation of the TiO 2 /Al 2 O 3 binary oxides via sol-gel method [16,18]. Three series of samples were prepared by varying the relative molar composition of the TiO 2 component in the TiO 2 /Al 2 O 3 binary oxide.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium (IV) isopropoxide (TIP, 97%, Sigma-Aldrich) and aluminum-tri-sec-butoxide (ASB, 97%, Sigma-Aldrich) were used as the main ingredients in the preparation of the TiO 2 /Al 2 O 3 binary oxides via sol-gel method [16,18]. Three series of samples were prepared by varying the relative molar composition of the TiO 2 component in the TiO 2 /Al 2 O 3 binary oxide.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This alternative strategy was inspired by our recent studies on NSR technology which is used for the thermal catalytic after treatment of automotive NO x emissions [12,[16][17][18][19][20][21]. In couple of these former studies, we spectroscopically demonstrated that [12,[16][17][18][19][20][21] on the TiO 2 /Al 2 O 3 binary oxide surface, oxidized NO x species such as NO 2 (g) can readily undergo a thermal disproportionation reaction forming adsorbed nitrites and nitrates allowing effective solid state NO x storage. However NO(g) has a limited adsorption energy on many metal oxide surfaces compared to that of NO 2 , hindering the storage of NO in the solid (adsorbed) state.…”
Section: Introductionmentioning
confidence: 99%
“…Calcination at 200 and 300 • C leads to the formation of an amorphous TiO 2 /TiO x structure, which starts to crystallize into a rather disordered anatase phase at 400 • C with a small average particle size, evident from the corresponding broad anatase XRD diffraction signals (ICDD Card No: 21-1272) in Fig. 4a and the characteristically intense anatase Raman scattering observed at 144 cm −1 [24][25][26]. At 500 • C, a well-ordered anatase phase with a larger average particle size is formed as can be seen from the sharp and intense anatase signals in both XRD (Fig.…”
Section: Structural Characterization Of Polymer-templated Tio 2 Micromentioning
confidence: 99%
“…4b. Formation of the rutile phase leads to the evolution of typical Raman scattering features at 236, 447, 612, 826 cm −1 [24][25][26]. Rutile phase becomes more crystalline and abundant at higher calcination temperatures.…”
Section: Structural Characterization Of Polymer-templated Tio 2 Micromentioning
confidence: 99%
See 1 more Smart Citation